Konflik Politik Desa: Studi tentang Relasi Kuasa Elite Desa Dinamika dan Jenis Konflik Pasca Pilkades di Desa Nanga Sake Kecamatan Ambalau Kabupaten Sintang Provinsi Kalimantan Barat - Faustinus Duwon Galih (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Villages are seen as "sexy" by local elites these days, with village politics seen as a potential platform for power. Law No. 6/2014 on Villages as a reference to develop underdeveloped areas with the maximum authority given to the village, is interpreted differently by a handful of elites in power in the village. The election of the village head in Nanga Sake Village, Ambalau Sub-district, Sintang Regency, became an arena for local actors to build sympathy and to maintain family reputation. Intrigue and black compaingn (black campaign), mobilizing all available potential is very common. This research, using a qualitative descriptive method, seeks to describe a symptom, event, incident that occurs at the present time. With the intention of interpreting the phenomena that occur and carried out by involving various existing methods such as observation, interviews, observation to the utilization of documents. The results of this study are latent conflicts rooted in revenge, the existence of old unsolved problems that make the conflict very intense. Supported by the strong economic dimension, positions, and jobs expected of prospective leaders in the village. The interest in controlling economic resources has encouraged citizens and political elites to be impatient, so that all means to achieve it can be taken, even if it is out of the frame of culture, ethics and leads to prolonged social conflict.